2012
DOI: 10.1186/1687-6180-2012-23
|View full text |Cite
|
Sign up to set email alerts
|

Recent multiscale AM-FM methods in emerging applications in medical imaging

Abstract: Amplitude-modulation frequency-modulation (AM-FM) decompositions represent images using spatially-varying sinusoidal waves and their spatially-varying amplitudes. AM-FM decompositions use different scales and bandpass filters to extract the wide range of instantaneous frequencies and instantaneous amplitude components that may be present in an image. In the past few years, as the understanding of its theory advanced, AM-FM decompositions have been applied in a series of medical imaging problems ranging from ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 95 publications
0
21
0
Order By: Relevance
“…Since cos(ϕ(x)) = cos(−ϕ(x)), there is an ambiguity in the definition of the instantaneous frequency ∇ϕ since ϕ can be replaced by −ϕ. To solve this problem, practitioners usually assume that the first component of the instantaneous frequency is positive (see [10] and references therein for more details). Under this additional assumption, our method yields an estimate of the amplitude and of the instantaneous frequency of an IMMF:…”
Section: Wavelet Analysis Of Bidimensional Spectral Linesmentioning
confidence: 99%
“…Since cos(ϕ(x)) = cos(−ϕ(x)), there is an ambiguity in the definition of the instantaneous frequency ∇ϕ since ϕ can be replaced by −ϕ. To solve this problem, practitioners usually assume that the first component of the instantaneous frequency is positive (see [10] and references therein for more details). Under this additional assumption, our method yields an estimate of the amplitude and of the instantaneous frequency of an IMMF:…”
Section: Wavelet Analysis Of Bidimensional Spectral Linesmentioning
confidence: 99%
“…Biomedical images are often dominated by strong nonstationary behavior that can be described using Multidimensional Amplitude Modulation-Frequency Modulation (AM-FM) models [1], [2]. The development of AM-FM models and applications have been documented in previous research reported in [3], [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 97%
“…A summary of several applications of the new multi-scale AM-FM methods can be found in the recently published survey paper [2].…”
Section: Introductionmentioning
confidence: 99%